Seasonal dynamics of airborne biomolecules influence the size distribution of Arctic aerosols - Eunho Jang; Ki-Tae Park; Young Jun Yoon; Kyoung-Soon Jang; Min Sung Kim; Kitae Kim; Hyun Young Chung; Mauro Mazzola; David Cappelletti; Bang Yong Lee (Environmental Science and Ecotechnology)
Organic matter is crucial in aerosol–climate interactions, yet the physicochemical properties and origins of organic aerosols remain poorly understood. Here we show the seasonal characteristics of submicron organic aerosols in Arctic Svalbard during spring and summer, emphasizing their connection to transport patterns and particle size distribution. Microbial-derived organic matter (MOM) and terrestrial-derived organic matter (TOM) accounted for over 90% of the total organic mass in Arctic aerosols during these seasons, comprising carbohydrate/protein-like and lignin/tannin-like compounds, respectively. In spring, aerosols showed high TOM and low MOM intensities due to biomass-burning influx in the central Arctic. In contrast, summer exhibited elevated MOM intensity, attributed to the shift in predominant atmospheric transport from the central Arctic to the biologically active Greenland Sea. MOM and TOM were associated with Aitken mode particles (<100 nm diameter) and accumulation mode particles (>100 nm diameter), respectively. This association is linked to the molecular size of biomolecules, impacting the number concentrations of corresponding aerosol classes. These findings highlight the importance of considering seasonal atmospheric transport patterns and organic source-dependent particle size distributions in assessing aerosol properties in the changing Arctic.